Aluminum−lithium alloy as a stable and reversible anode for lithium batteries. (1st February 2021) - Chen, Shang; Yang, Xinyue; Zhang, Jie; Ma, Junpeng; Meng, Yongqiang; Tao, Kangjia; Li, Feng; Geng, Jianxin
Highlight: Al−Li alloy electrodes avoid the formation of lithium dendrites. Al−Li alloy electrodes show high reversibility due to pre-lithiation. The usability of Al−Li alloy anodes in full cells is confirmed using sulfur and LiFePO4 cathodes. Abstract: Li metal is a potential anode for lithium batteries owing to its high theoretical capacity (3860 mA h g − 1 ); however, its practical use is handicapped by the formation of dendrites. Herein, we propose an Al−Li alloy as a stable and reversible anode achieved via pre-lithiation of Al foil. The Al−Li alloy has a chemical composition of LiAl, giving a theoretical capacity of 993 mA h g − 1, which is 2.67 times higher than that of graphite. Because of the pre-lithiation effect and the preserved mosaic-like morphology, the polarization associated with Li plating on an Al−Li alloy electrode is much smaller than that observed on a pristine Al foil electrode, and is just 1/10 as that recorded on a Li foil electrode. As a result, with fast kinetics, the Al−Li alloy electrode shows superiorly high reversibility. Importantly, the usability of Al−Li alloy as anodes is confirmed using sulfur and LiFePO4 as cathodes in full cells. Graphical abstract: An aluminum−lithium (Al−Li) alloy is demonstrated to be a stable and reversible anode owing to the low polarization associated to Li plating on an Al−Li alloy electrode due to the pre-lithiation and preserved mosaic-like morphology. With constant lithiation/delithiation potentials, the Al−Li alloy anode exhibits a greater Li-ion diffusion coefficient than those of Sn- and Si-based alloys. The usability of the Al−Li alloy as an anode is verified in lithium−sulfur batteries and Li-ion batteries. Image, graphical abstract